DYNAMICS OF LAND USE IN PERMANENT PRESERVATION AREAS ALONG THE UPPER COURSE OF RIBEIRAO DOS RANCHOS BASIN - ADAMANTINA/SP - Kohori, Carolina Bugalho [UNESP]; Piroli, Edson Luis [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2018)
Nova Alta Paulista was one of the latest regions to be crossed by the railroad and occupied by the coffee crop with its natural landscape almost totally suppressed by the expansion of the urban area and the agricultural crops. The municipalities were built in the watershed of Aguapei and Peixe rivers, occupying several springs of streams. Due to this reality, it was proposed the analysis of the dynamics in the permanent preservation areas along the upper course of Ribeirao dos Ranchos basin, which is located in the municipality of Adamantina, a member of Nova Alta Paulista. The objective of this study was to analyze the changes in land use in PPAs from 1971 to 2016, and their respective environmental impacts on this area, using geo-processing techniques. It was observed throughout the analyses, that there were significant changes, such as the decrease of the temporary tillage class and the expansion of the pasture areas. The main environmental problems observed in the rural area were degraded pasturelands, the absence of riparian forest, eroded soils, the sedimentation and contamination of water resources. However, it was noted a small progress within the forest coverage in the areas of permanent preservation.
Keywords: Geo-processing; Remote sensing; Environmental impacts; Natural resources